The Effect of Profitability and Profit Management on Corporate Income Tax Payable (Empirical Study On IDX Manufacturing Companies 2015-2020) - Lestinar Fefrina; Muhammad Nur; Kumba Digdowiseiso (Jurnal Syntax Transformation, 2024)
This study aims to analyze Profitability and Ernings Management on Income Tax (Pph) of Agency Payable of pharmaceutical Industry companies listed on the Indonesia Stock Exchange (IDX). This research use library data collection rechniques and documentary studies, the sample in this study amounted to 11 pharmaceutical industry companies listed on the Indonesia stock Exchange (IDX) in 2015-2020, the data analysis technique used in this study is associative analysis technique. The data in this study are in the form of annual financial statements,closing price of shares,&; the number of outstanding shares listed on the Indonesia stock Exchange (IDX) website. Based on the results of the analysis, it can be seen the Profitability has no effect on Corporate Income Tax (Pph) Payable with a significant value of 0,324, while the Earnings Management Variable has no significant effevt on Corporate Income Tax (Pph) payable with a value of 0,067. From the results pf the coefficient of determination, the results is 0,031. This means that 3,1% of the Comporate Income tax (Pph) Variable payable can be explained by Profitability and Earnings Management. While the remaining 96,9% can be explained by other factors other than the independent variable used.